Composite diaphragm manufacturing process and products made therefrom
The composite diaphragm fabrication process addresses the issue of insufficient sealing in putty packaging bags by using a primer-coated kraft paper and intaglio-printed overcoat layer, resulting in a stable and airtight packaging solution that extends the shelf life of putty powder.
Patent Information
- Application Number
- JP2024161135
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-08-21
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-17
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Conventional putty packaging bags experience insufficient sealing, leading to moisture and air ingress, which causes putty to deteriorate. The existing sewing and adhesive sealing methods are ineffective in maintaining the dryness and purity of the putty powder.
A composite diaphragm fabrication process involving inverted coating of a primer on kraft paper to create a smooth surface, followed by intaglio printing for a discontinuous overcoat layer. The kraft paper composite layer is then combined with the composite substrate layer via wet lamination, and the undercoat and topcoat layers are bonded using pressurizing rollers, forming a stable composite diaphragm with improved sealing properties.
The process results in a composite diaphragm that effectively prevents water and air from entering the packaging bag, thereby extending the shelf life of the putty powder and maintaining its quality. The smooth surface of the primer layer prevents putty powder adherence, while the bonded layers ensure stable and durable sealing.
Smart Images

Figure 0007663999000005 
Figure 0007663999000001 
Figure 0007663999000002
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This application relates to the field of composite film processing technology, and more specifically, to composite diaphragm fabrication processes and resulting products. [Background technology]
[0002] Putty packaging bags can prevent the putty powder from being damp or polluted, and keep its dryness and purity. Putty powder packaging bags are usually made by compounding multi-layer materials, mainly including an outer layer material, an inner layer material, and a middle isolation layer, the outer layer material and the inner layer material are usually kraft paper, and the middle layer material is usually PE film, such a composite film can effectively protect the putty powder from dampness and pollution, and the inner layer kraft paper is compounded with the PE film to form a packaging structure with good airtightness, which can prevent air and water from entering, and maintain the quality and stability of the putty powder.
[0003] In the actual process of use, the putty may discolor, harden, or coagulate, the main reason being that the seal is insufficient when the putty packaging bag is sealed. Conventional putty packaging bags are mainly sealed by sewing, and the bottom or side of the packaging bag is sewn with high-strength fiber thread to seal it, but this can allow water and air to enter the packaging bag at the sealed portion, causing the putty to deteriorate.
[0004] In order to prevent water and air from entering the sealed portion, hot melt adhesive or glue is used to seal the package. In the process of gluing, generally, putty powder is added first and then gluing is performed. In the process of addition, the putty powder adheres to the surface of the kraft paper, which affects the adhesion stability of the hot melt adhesive or glue. After a long time, water and air may still enter the packaging bag, which may adversely affect the quality of the putty. Secondly, because the surface of the kraft paper is uneven, when gluing with glue or hot melt adhesive, the glue or hot melt adhesive cannot completely fill the pores on the surface of the kraft paper, which may cause the adhesion by the hot melt adhesive or glue to be unstable. As the storage time increases, water and air may enter the packaging bag through the pores, which may affect the quality of the putty powder. Summary of the Invention
[0005] To solve the problem of water and air getting into the seal when sealing the putty packaging bag, the present application provides a composite diaphragm fabrication process and the resulting product.
[0006] In a first aspect, the present application provides a composite diaphragm manufacturing process using the following technical solutions:
[0007] 1. A composite diaphragm fabrication process comprising the steps of: S1, a primer is reverse-coated on the kraft paper surface of the composite film to form a primer layer and obtain a kraft paper composite layer; S2, the substrate screen-printed surface is coated by intaglio printing to form a discontinuous topcoat layer to obtain a composite substrate layer; S3, in which the kraft paper composite layer is combined with the composite substrate layer by wet lamination, and then the undercoat layer and the topcoat layer are bonded together by a pressure roller to obtain a composite diaphragm, where the wet lamination means that the undercoat layer and the topcoat layer are bonded together in a state where neither of them is completely cured; The undercoat agent is prepared from polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, castor oil polyol, hardener and diluent; The topcoat is made of polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, nanoscale rubber powder, hardener and diluent to obtain a composite diaphragm fabrication process.
[0008] By using the above technical solution, the surface of the kraft paper can be made smooth and flat, making it difficult for the putty powder to stick to it, so that the seal of the putty powder packaging bag can be stabilized, making it difficult for water and air to enter, and extending the shelf life of the putty powder.
[0009] First, the undercoat is applied by the reverse coating method, so that the undercoat penetrates into the kraft paper and fills the pores of the kraft paper, preventing air and water from entering the putty packaging bag through the kraft paper, and at the same time, preventing the putty powder from adhering to the surface of the undercoat layer when filling the putty powder, which contributes to the sealing stability of the putty packaging bag later. In the undercoat, the glycidyl ester type epoxy resin bonds with the hydroxyl group on the kraft paper when cured, so that the undercoat layer can be stably attached to the kraft paper, and at the same time, contributes to the bonding with the topcoat layer, improving the stability of the composite diaphragm. Methylcellulose improves the fluidity of the primer, so that the primer can more easily penetrate into the kraft paper and fill the pores of the kraft paper, while at the same time making the surface of the primer smoother and less likely to cause putty powder to adhere; castor oil polyol contributes to improving the flexibility and adhesion of the glycidyl ester type epoxy resin, further improving the adhesion of the primer to the kraft paper, while at the same time improving the structural stability of the primer layer, making it less likely to be damaged during use.
[0010] Both the topcoat and undercoat contain polylactic acid emulsion, methylcellulose and glycidyl ester type epoxy resin, which contributes to the mutual bonding between the topcoat and undercoat, making the topcoat layer and undercoat layer firmly bonded and difficult to peel off. The reason is that the topcoat layer and undercoat layer are attached together in an uncured state, and after pressing, the components of both layers fuse together, and a curing reaction occurs during the later curing, forming a stable network structure, realizing a stable bond between the undercoat layer and the topcoat layer, and preventing the undercoat layer and the topcoat layer from separating.
[0011] The topcoat layer is in direct contact with the putty, and the topcoat layer must not only have good airtight waterproof effect, but also have good chemical resistance to prevent corrosion caused by the putty. The main reason why many conventional putty packaging bags have a short service life is that the inside of the packaging bag ages due to corrosion caused by the putty powder, which causes leakage. In this application, the topcoat layer is made of polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, nanoscale rubber powder, hardener and diluent, so that the airtight waterproof effect, chemical resistance and corrosion resistance of the topcoat layer can be comprehensively improved, and the putty can be protected from corrosion and destruction by the external environment. The nanoscale rubber powder plays the role of filling, reinforcing and corrosion prevention in the coating layer, and its fine particle size allows it to be uniformly distributed in the coating layer to form an effective reinforcing phase, which can further improve the airtight waterproof effect, chemical resistance and corrosion resistance of the topcoat layer. The putty powder packaging bag in this application can be reused many times.
[0012] In step S2, intaglio printing creates a discontinuous, smooth overcoat layer on the substrate, which aids in subsequent transfer.
[0013] In step S3, the kraft paper composite layer is first combined with the composite substrate layer by wet lamination, and then pressed together, so that the topcoat layer is transferred onto the undercoat layer, and the substrate layer can be simply peeled off when in use.
[0014] Preferably, the substrate is an OPP film or a PE film.
[0015] The use of the above technical proposal contributes to subsequent peeling. Both OPP film and PE film are smooth, non-sticky, raised materials that are easy to peel off as substrates.
[0016] Preferably, the primer is made from the following weight percentages of ingredients: 20-30% polylactic acid emulsion, 4-6% methylcellulose, 10-15% glycidyl ester type epoxy resin, 6-10% castor oil polyol, 1-2% hardener, The remainder is the diluent.
[0017] By using the above technical solution, the amount of primer raw material prepared is optimized, so that the wettability and fluidity of the primer is further increased, which is conducive to filling the inside of the kraft paper and preventing water and air from entering the inside of the packaging bag. At the same time, it can be fully bonded with the topcoat layer to form a stable bonding layer, and the putty powder will not stick after drying.
[0018] Preferably, the topcoat is made from the following weight percentages of ingredients: 20-30% polylactic acid emulsion, 4-6% methylcellulose, 10-15% glycidyl ester type epoxy resin, 5-8% nanoscale rubber powder, 1-2% hardener, The remainder is the diluent.
[0019] By using the above technical solution, the weight ratio of the topcoat raw materials can be optimized, the chemical resistance performance of the topcoat can be improved, the leakage of putty powder can be prevented, and at the same time, the topcoat can be sufficiently bonded with the undercoat layer to form a stable bonding layer, and the durability of the composite diaphragm can be improved.
[0020] Preferably, the glycidyl ester type epoxy resin has 2 to 4 functional groups and an epoxy value of 0.5 to 0.9.
[0021] The above technical solution improves the adhesion stability between the undercoat layer and the kraft paper layer, and at the same time makes the undercoat layer more dense, preventing water and air from entering the putty powder packaging bag. In addition, the appropriate functional group and epoxy value can ensure that the coating layer maintains a certain hardness and strength, while having good flexibility and crack resistance, so as to contribute to the packaging according to the needs of folding and bending of the kraft paper.
[0022] Preferably, the polylactic acid emulsion is prepared by the following method: 1) Dissolve 20-30 parts of polylactic acid in 60-70 parts of a solvent by weight to obtain a clear solution. 2) Calculated by weight, 2-3 parts of water-soluble emulsifier is added to 30-40 parts of deionized water, stirred until dissolved, and then 5-10 parts of water-soluble chitosan is added to obtain a mixed liquid. 3) The clear solution and the mixed liquid are stirred at high speed at 1000 to 1500 r / min to obtain a polylactic acid emulsion.
[0023] By using the above technical solution, the dispersibility of polylactic acid is further improved, so that polylactic acid can be fully and uniformly mixed with glycidyl ester type epoxy resin in the primer system and topcoat system, forming a more uniform and stable system, which is conducive to the application of the primer and topcoat.
[0024] The clear solution obtained in step 1 is slowly added to the mixed solution obtained in step 2. During the addition, a high-speed stirrer is used to stir at a speed of 1000 to 1500 revolutions per minute. High-speed stirring disperses the polylactic acid solution into fine droplets, which are stably dispersed in the aqueous phase by the action of the emulsifier and water-soluble chitosan, thereby forming a polylactic acid emulsion, which provides good fluidity to the polylactic acid emulsion and contributes to thorough mixing with the glycidyl ester type epoxy resin.
[0025] Preferably, the nanoscale rubber powder has an average particle size of 50 to 300 nm.
[0026] By using the above technical solution, the particle size of the nano-rubber powder can be optimized, the nano-rubber powder can be uniformly distributed in the topcoat system, and the chemical resistance and water and air barrier properties of the topcoat layer can be improved.
[0027] Preferably, the castor oil polyol is obtained by mixing a castor oil polyol having a hydroxyl value of 55 to 60 mgKOH / g, a castor oil polyol having a hydroxyl value of 70 to 100 mgKOH / g, and a castor oil polyol having a hydroxyl value of 100 to 150 mgKOH / g in a weight ratio of (8-10):(4-6):3.
[0028] By using the above technical solution, the wetting and adhesion properties of the undercoat layer can be improved, while at the same time the crosslink density and toughness of the coating can be improved, which contributes to improving the drop resistance of the composite diaphragm. Castor oil polyols with low hydroxyl values (55-60mgKOH / g) usually contain long fatty acid chains, which contribute to increasing the flexibility of the coating. Castor oil polyols with high hydroxyl values (70-100mgKOH / g and 100-150mgKOH / g) contain more hydroxyl groups, which generate more crosslinking reactions with the curing agent during curing, thus improving the crosslink density of the coating and reducing the ingress of water and air.
[0029] Preferably, the coating speed in step S1 is 40 to 60 m / min and the pressure is 20 to 25 MPa.
[0030] The above technical solution can stably and uniformly coat the primer on the kraft paper, while improving the density and adhesion of the primer layer. If the pressure is too low, the primer will be distributed unevenly, resulting in a rough surface of the coating layer; if the pressure is too high, the primer will splash out, causing waste and affecting the quality of the primer layer.
[0031] Preferably, in step S3, the temperature of the pressure roller is 110 to 120° C., the pressure of the pressure roller is 15 to 20 MPa, and the speed of the pressure roller is 20 to 25 m / min.
[0032] By using the above technical solution, the topcoat layer and the undercoat layer can be stably connected, and the transition of the topcoat layer can be realized. If the temperature of the pressure roller is too high, the hardening of the undercoat layer and the topcoat layer will be accelerated, and the two will harden even if they are not completely fused together, which may affect the connection stability of the undercoat layer and the topcoat layer. If the temperature is too low, the connection of the topcoat layer and the undercoat layer will not be reliable, and with appropriate pressure, the topcoat layer and the undercoat layer can be fully compressed, improving the density and strength of the product. If the pressure is too high, the material may crack or deform, and if the pressure is too low, the compression may be insufficient.
[0033] In a second aspect, the present application provides a composite diaphragm using the following technical solution:
[0034] A composite diaphragm comprising a composite film, an undercoat layer connected to a surface of a kraft paper layer of the composite film, and a topcoat layer, the overcoat layer comprising a first overcoat layer and a second overcoat layer arranged symmetrically on the surface of the undercoat layer, and neither an edge of the first overcoat layer nor an edge of the second overcoat layer overlaps an edge of the undercoat layer.
[0035] The composite diaphragm is obtained by the composite diaphragm manufacturing process described in the first embodiment.
[0036] By using the above technical solution, the composite diaphragm undercoat layer obtained does not adhere to the putty powder and does not affect the subsequent sealing. At the same time, the structure of the composite diaphragm is stable, has excellent barrier properties, excellent chemical resistance, is resistant to falling, is convenient for packaging the putty powder, and greatly extends the packaging time of the putty powder.
[0037] In summary, the present application has the following beneficial effects:
[0038] By applying the primer on the surface of the kraft paper of the composite film by reverse coating, the primer can penetrate into the kraft paper and fill its pores, improving the density and barrier properties of the kraft paper. Polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, castor oil polyol, hardener and diluent are jointly prepared as the primer, which ensures that the primer layer does not stick to the putty and contributes to the sealing of the packaging bag later. Polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, nano-scale rubber powder, hardener and diluent are prepared as the top coat layer, which improves the airtight waterproof effect, chemical resistance and corrosion resistance of the top coat layer, and protects the putty from erosion and destruction caused by the external environment. At the same time, the primer layer and the top coat layer are bonded by the wet method to form a strong bond layer, which effectively prevents air and water from entering the packaging bag, improves the structural stability and airtight waterproof of the composite membrane, and extends the storage time of the putty powder. [Brief description of the drawings]
[0039] [Figure 1] FIG. 1 is a structural schematic diagram of a composite diaphragm in the first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] Example of production The water-soluble chitosan is a commercially available carboxylated chitosan with a degree of carboxylation of 80%. Preparation example 1
[0041] A polylactic acid emulsion, which is produced by the following method: 1) Dissolve 200 g of polylactic acid in 600 g of solvent (dihydramide) to obtain a clear solution; 2) 20 g of a water-soluble emulsifier (glycerol monostearate) is added to 300 g of deionized water and stirred until dissolved, and then 50 g of water-soluble chitosan is added to obtain a mixed liquid. 3) The clear solution and the mixed liquid are stirred at a high speed of 1000 r / min to obtain a polylactic acid emulsion. Preparation examples 2-3
[0042] The differences from Preparation Example 1 are in the types, amounts, and experimental parameters of some of the raw materials used to prepare the polylactic acid emulsion. Specific differences are shown in Table 1.
[0043] Table 1 Experimental data for Preparation Examples 1 to 3 JPEG0007663999000001.jpg65166 Example Example 1
[0044] As shown in Fig. 1, the composite diaphragm includes a composite film 1, a base coat layer 2 connected to the surface of the kraft paper layer of the composite film 1, and a top coat layer 3, the top coat layer 3 includes a first top coat layer and a second top coat layer symmetrically arranged on the surface of the base coat layer 2, and the edge of the first top coat layer and the edge of the second top coat layer do not overlap the edge of the base coat layer 2. The area of the first top coat layer and the second top coat layer is 10cm*20cm, the area of the base coat layer 2 is 14*50cm, and the distance between the first top coat layer and the second top coat layer is 5cm. The distance between the long edge of the first top coat layer and the long edge of the base coat layer 2 is 2cm, and the distance between the wide edge of the first top coat layer and the wide edge of the base coat layer 2 is 2.5cm.
[0045] The composite diaphragm is produced in the following manner.
[0046] S1: The primer is reverse-coated on the kraft paper surface of the composite film to form a primer layer. The coating speed is 40 m / min, the coating pressure is 20 MPa, and the coating moisture content is 6 g / m 2 and a kraft paper composite layer is obtained.
[0047] S2: The screen-printed surface of the substrate is coated by intaglio printing to form a discontinuous topcoat layer, and a composite substrate layer is obtained.
[0048] S3: The kraft paper composite layer is combined with the composite substrate layer by wet lamination, and then the pressure roller is applied to the composite substrate layer at a pressure roller speed of 20 m / min, a pressure roller pressure of 15 MPa, and a coating moisture content of 10 g / m 2 The undercoat layer and the topcoat layer are bonded together to obtain a composite diaphragm, and the term "wet lamination" means that the undercoat layer and the topcoat layer are bonded together in a state where neither of them is completely cured.
[0049] The primer is prepared from 200 g of polylactic acid emulsion (from Preparation Example 1), 40 g of methylcellulose, 100 g of glycidyl ester type epoxy resin, 60 g of castor oil polyol, 10 g of hardener (triglycidyl isocyanurate) and 300 g of diluent (alkylene glycidyl ether).
[0050] The topcoat is prepared from 200 g of polylactic acid emulsion (from Preparation Example 1), 40 g of methylcellulose, 100 g of glycidyl ester type epoxy resin, 50 g of nanoscale rubber powder, 10 g of hardener (triglycidyl isocyanurate) and 300 g of diluent (alkylene glycidyl ether).
[0051] The glycidyl ester type epoxy resin is a diglycidyl adipate type epoxy resin, with a functional group of 2 and an epoxy value of 0.5.
[0052] The hydroxyl value of the castor oil polyol is 55 mg KOH / g.
[0053] The nanoscale rubber powder has an average particle size of 50nm, is nitrile rubber, the brand is Kaiming Plastics, and the type is SH-830.
[0054] The substrate is a PE film. Examples 2 to 3
[0055] The differences from Example 1 are in the types, amounts, and experimental parameters of some of the raw materials used to produce the composite diaphragm. Specific differences are shown in Table 2.
[0056] Table 2 Experimental data for Examples 1 to 3 JPEG0007663999000002.jpg221163Example 4
[0057] This composite diaphragm differs from Example 1 in that the castor oil polyol is obtained by mixing a castor oil polyol having a hydroxyl value of 55 mgKOH / g, a castor oil polyol having a hydroxyl value of 70 mgKOH / g, and a castor oil polyol having a hydroxyl value of 100 mgKOH / g in a weight ratio of 8:4:3. Example 5
[0058] This composite diaphragm differs from Example 1 in that the castor oil polyol is obtained by mixing a castor oil polyol with a hydroxyl value of 60 mgKOH / g, a castor oil polyol with a hydroxyl value of 100 mgKOH / g, and a castor oil polyol with a hydroxyl value of 150 mgKOH / g in a weight ratio of 10:6:3. Example 6
[0059] This composite diaphragm differs from Example 1 in that the castor oil polyol is obtained by mixing a castor oil polyol with a hydroxyl value of 55 mg KOH / g and a castor oil polyol with a hydroxyl value of 70 mg KOH / g in a weight ratio of 8:7. Example 7
[0060] This composite diaphragm differs from Example 1 in that the castor oil polyol is obtained by mixing a castor oil polyol with a hydroxyl value of 55 mg KOH / g and a castor oil polyol with a hydroxyl value of 100 mg KOH / g in a weight ratio of 8:7. Example 8
[0061] This composite diaphragm differs from Example 1 in that the castor oil polyol is obtained by mixing a castor oil polyol with a hydroxyl value of 70 mg KOH / g and a castor oil polyol with a hydroxyl value of 100 mg KOH / g in a weight ratio of 4:11. Example 9
[0062] The difference between this embodiment and the first embodiment of the composite diaphragm is that the coating speed in step S1 is 40 m / min and the pressure is 15 MPa. Example 10
[0063] The composite diaphragm in this embodiment differs from that in Example 1 in that in step S3, the temperature of the pressure roller is 130° C., the pressure of the pressure roller is 15 MPa, and the speed of the pressure roller is 20 m / min. Example 11
[0064] The composite diaphragm in this embodiment differs from that in Example 1 in that in step S3, the temperature of the pressure roller is 110° C., the pressure of the pressure roller is 10 MPa, and the speed of the pressure roller is 20 m / min. Comparative Example Comparative Example 1
[0065] This is a composite diaphragm, and the difference between this comparative example and Example 1 is that there is no undercoat layer. Comparative Example 2
[0066] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that a sequential coating method is used in step S1. Comparative Example 3
[0067] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that screen printing is used in step S2. Comparative Example 4
[0068] The difference between this comparative example and Example 1 in the composite diaphragm is that the undercoat layer and the topcoat layer are completely cured in step S3. Comparative Example 5
[0069] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that an acrylic polymer emulsion is used in place of a polylactic acid emulsion in the undercoat.
[0070] The acrylic polymer emulsion is Dow Acrylic Polymer Emulsion PRIMAL NW-5118 acrylic emulsion. Comparative Example 6
[0071] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that an aliphatic epoxy resin is used in the undercoat agent instead of a glycidyl ester type epoxy resin.
[0072] The aliphatic epoxy resin is Dow Aliphatic Flexible Epoxy Resin DER732. Comparative Example 7
[0073] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that carboxymethyl cellulose is used in place of methyl cellulose in the undercoat. Comparative Example 8
[0074] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that a polyether polyol is used in place of the castor oil polyol in the undercoat agent.
[0075] The molecular weight of the polyether polyol is 5,000. Comparative Example 9
[0076] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that silica is used in the topcoat instead of nanoscale rubber powder. Comparative Example 10
[0077] This is a composite diaphragm, and the difference between this comparative example and Example 1 is that the particle size of the rubber powder is 1 μm. Comparative Example 11
[0078] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that an acrylic polymer emulsion is used in place of a polylactic acid emulsion in the topcoat.
[0079] The acrylic polymer emulsion is Dow Acrylic Polymer Emulsion PRIMAL NW-5118 acrylic emulsion. Comparative Example 12
[0080] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that an aliphatic epoxy resin is used in the topcoat instead of a glycidyl ester type epoxy resin.
[0081] The aliphatic epoxy resin is Dow Aliphatic Flexible Epoxy Resin DER732. Comparative Example 13
[0082] This comparative example is a composite diaphragm, and the difference between this comparative example and Example 1 is that BASF Joncryl HPB is used instead of the primer. Detection / Testing Methods
[0083] Adhesion putty powder test: After peeling off the substrate from the composite diaphragms produced in Examples 1 to 11 and Comparative Examples 1 to 13, each was immersed in putty powder, kept for 1 minute, then taken out and shaken to observe whether the putty powder adheres to the surface of the undercoat layer. If the powder adheres, the test experiment is no longer necessary.
[0084] Sealing test: If no putty powder remains in the adhesion putty powder test, continue to the sealing test. Apply adhesive to the undercoated surface, fold along the center line of the undercoat layer without applying adhesive to one side, and press together to form a packaging bag, and form a seal without applying adhesive to the other side, then add 15g of putty powder, apply the adhesive to the seal, seal, weigh, put it into 80℃ water and soak for 20 days, take it out, wipe off the water, weigh, and calculate the weight increase.
[0085] Adhesion stability test of the kraft paper layer, undercoat layer and topcoat layer: After peeling off the substrate from the composite diaphragms produced in Examples 1 to 11 and Comparative Examples 1 to 13, immerse them in 15% hydrogen peroxide by mass fraction, soak for 5 days, remove, wipe off the water, fix them in place, and again use a dryer to blow air along the sides, setting the air speed to 50 m / s, and blow for 1 hour to observe whether separation occurs between the layers.
[0086] Chemical resistance test: peel off the substrate, apply adhesive to the undercoat layer, fold one side along the center line of the undercoat layer without applying adhesive, and press together to form a packaging bag, and form a seal on the other side without applying adhesive, then add half the volume of 20% mass concentration sodium hydroxide solution, apply the adhesive to the seal, seal, and place in an environment with a humidity of 90% and a temperature of 80°C, record the leakage time of the packaging bag, and record it for up to 1000 hours. When there is no leakage, stop the test and record that there is no leakage.
[0087] Drop resistance test: peel off the substrate, apply adhesive to the undercoat layer, do not apply adhesive to one side, fold along the center line of the undercoat layer, press together to form a packaging bag, do not apply adhesive to the other side to form a seal, then add half the volume of putty powder, and apply the adhesive to the seal, take a sample, choose a smooth concrete ground, and let the sample fall from a height of 3m to observe whether the packaging bag is damaged. The experimental data is shown in Table 3.
[0088] Table 3 Experimental data for Examples 1 to 11 and Comparative Examples 1 to 13 JPEG0007663999000003.jpg247146JPEG0007663999000004.jpg22146
[0089] Comparing Example 1 with Comparative Examples 1 to 4, Comparative Example 1 has a situation where adhesive putty occurs in the adhesive putty powder test, Comparative Examples 2 to 4 have a significantly larger weight increase than Example 1 in the airtightness test, and Comparative Example 2 has the largest increase. In the adhesive stability test of the kraft paper layer, the undercoat layer, and the topcoat layer, Comparative Examples 2 to 3 have a situation where the kraft paper and the undercoat layer separate, and Comparative Example 4 has a situation where the undercoat layer and the topcoat layer separate. In the chemical resistance test, Comparative Examples 2 to 4 have an obviously short time for leakage to occur. From the results of Comparative Examples 1 to 4 and Example 1, the composite diaphragm produced by the production process in the present application is less likely to have non-adhesive putty powder adhered to it and is easy to seal, and at the same time has good structural stability, barrier properties, chemical resistance, and drop resistance.
[0090] As can be seen from the results of Comparative Examples 5 to 8 and Example 1, by using polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin and castor oil polyol as the undercoat agent, it is possible to effectively prevent the putty from adhering to the undercoat layer, and at the same time, it is possible to effectively improve the structural stability, barrier properties, chemical resistance and drop resistance of the composite diaphragm.
[0091] As can be seen from the results of Comparative Examples 9 to 12 and Example 1, by preparing a composite diaphragm using polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, and nanoscale rubber powder as a topcoat, the structural stability, barrier properties, chemical resistance, and drop resistance of the composite diaphragm can be effectively improved.
[0092] As can be seen by comparing Example 1 with Comparative Example 13, in the present application, the undercoat layer does not allow the putty powder to adhere.
[0093] As can be seen by comparing Example 1 with Examples 4 to 8, the barrier properties and chemical resistance of the composite diaphragm can be effectively improved by mixing castor oil polyester polyols with different hydroxyl values.
[0094] As can be seen from the comparison of Example 1 with Examples 9 to 11, by optimizing the speed of the primer and the temperature of the pressure roller, the barrier properties, chemical resistance and structural stability of the composite diaphragm can be effectively improved.
[0095] The specific examples are merely illustrative of the present application and do not limit the present application. After reading this specification, a person skilled in the art may make amendments to the present examples as necessary without making any creative contribution thereto, but as long as they are within the scope of the claims of this application, they shall be protected by the Patent Law. [Explanation of symbols]
[0096] 1 Composite film 2 Undercoat layer 3 Topcoat
Claims
1. 1. A composite diaphragm fabrication process comprising the steps of: Step S1: applying a primer to the kraft paper surface of the composite film to form a primer layer and obtain a kraft paper composite layer; A step S2 of coating the substrate screen printing surface by intaglio printing to form a discontinuous topcoat layer made of a topcoat agent to obtain a composite substrate layer; and step S3 of combining the kraft paper composite layer with the composite substrate layer by wet lamination, and then bonding the undercoat layer and the topcoat layer with a pressure roller to obtain a composite diaphragm, where wet lamination means that the undercoat layer and the topcoat layer are bonded together in a state where neither of them is completely cured. The undercoat agent is prepared from polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, castor oil polyol, hardener and diluent; The topcoat is made from polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, nanoscale rubber powder, hardener and diluent. A process for fabricating a composite diaphragm comprising:
2. The primer is made from the following weight percentages of ingredients: 20-30% polylactic acid emulsion, 4-6% methylcellulose, 10 to 15% glycidyl ester type epoxy resin, 6-10% castor oil polyol, 1-2% hardener, The remainder is diluent 2. The process for making a composite diaphragm according to claim 1.
3. The topcoat is made from the following weight percentages of ingredients: 20-30% polylactic acid emulsion, 4-6% methylcellulose, 10 to 15% glycidyl ester type epoxy resin, 5-8% nanoscale rubber powder, 1-2% hardener, The remainder is diluent 2. The process for making a composite diaphragm according to claim 1.
4. The glycidyl ester type epoxy resin has 2 to 4 functional groups and an epoxy value of 0.5 to 0.9 mol / 100 g.
2. The process for making a composite diaphragm according to claim 1.
5. The polylactic acid emulsion is produced by the following method: 1) Dissolve 20-30 parts of polylactic acid in 60-70 parts of a solvent, by weight, to obtain a clear solution; 2) Calculate by weight and add 2-3 parts of water-soluble emulsifier to 30-40 parts of deionized water, stir until dissolved, and then add 5-10 parts of water-soluble chitosan to obtain a mixed liquid; 3) The clear solution and the mixed solution are stirred at high speed at 1000 to 1500 r / min to obtain a polylactic acid emulsion.
2. The process for making a composite diaphragm according to claim 1.
6. The nanoscale rubber powder has an average particle size of 50 to 300 nm.
2. The process for making a composite diaphragm according to claim 1.
7. The castor oil polyol is obtained by mixing a castor oil polyol having a hydroxyl value of 55 to 60 mgKOH / g, a castor oil polyol having a hydroxyl value of 70 to 100 mgKOH / g, and a castor oil polyol having a hydroxyl value of 100 to 150 mgKOH / g in a weight ratio of (8 to 10):(4 to 6):
3.
2. The process for making a composite diaphragm according to claim 1.
8. The coating speed in step S1 is 40 to 60 m / min, and the pressure is 20 to 25 MPa.
2. The process for making a composite diaphragm according to claim 1.
9. In step S3, the temperature of the pressure roller is 110 to 120° C., the pressure of the pressure roller is 15 to 20 MPa, and the speed of the pressure roller is 20 to 25 m / min.
2. The process for making a composite diaphragm according to claim 1.
10. 1. A composite diaphragm comprising: The composite diaphragm comprises a composite film, an undercoat layer connected to a surface of the kraft paper layer of the composite film, and a topcoat layer, the topcoat layer comprising a first topcoat layer and a second topcoat layer symmetrically provided on the surface of the undercoat layer, and neither an edge of the first topcoat layer nor an edge of the second topcoat layer overlaps an edge of the undercoat layer; The composite diaphragm is obtained by the composite diaphragm manufacturing process according to any one of claims 1 to 9. A composite diaphragm comprising:
Citation Information
Patent Citations
Paper laminate and method for producing the same
JP2022169426A
Paper laminate and method for manufacturing same
JP2022169497A
Heat-sealable paperboard structures and methods
JP2023511176A
Compostable compositions, articles, and methods for making compostable articles
JP2023521231A